The Relationship between Zooplankton Abundance with Phytoplankton and Physic-Chemistry Parameters at Kastela Waters, Ternate - Yuliana, Yuliana; Mutmainnah, Mutmainnah (Torani Journal of Fisheries and Marine Science, 2019)
Zooplankton has an important role in waters, especially in the food chain, these organisms are consumers I which play a major role in bridging energy transfer from major producers (phytoplankton) to living things at higher trophic levels (fish and shrimp). This study aims to analyze the relationship between zooplankton abundance with phytoplankton and physicochemical parameters in the waters of Kastela, Ternate. The research was conducted from March to April 2017 in the waters of Kastela Ternate City North Maluku Province at 5 stations and 4 periods of sampling. Zooplankton samples were taken by filtering methods. The results showed that there were 20 zooplankton genera from 5 (five) classes namely Ciliate (4 genera), Crustaceae (8 genera), Hydrozoa (3 genera), Rotifera (3 genera), and Urocohordata (2 genera). Zooplankton abundance ranges from 1032 to 10942 cells.l-1, the highest at station 3 periods II (10942 cells.l-1), and the lowest at station 4 period I (1032 cells l-1). The range of values of the zooplankton biological indices is diversity index (0.5005 - 1.8662), uniformity index (0.6521 - 0.9601), and dominance index (0.1661 - 0, 6800). There was a low correlation between zooplankton abundance and phytoplankton abundance and physical-chemical parameters of water in Kastela waters, with determination coefficient is 0.236 and regression equation Y = 35079.107 + 0.030 phytoplankton - 791,251 temperature + 75,417 salinity - 1658,557 pH Keywords: mangroves, macrozoobenthics, organic matter